2015
DOI: 10.1073/pnas.1500873112
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of phosphonic acid natural products by mining the genomes of 10,000 actinomycetes

Abstract: Although natural products have been a particularly rich source of human medicines, activity-based screening results in a very high rate of rediscovery of known molecules. Based on the large number of natural product biosynthetic genes in microbial genomes, many have proposed "genome mining" as an alternative approach for discovery efforts; however, this idea has yet to be performed experimentally on a large scale. Here, we demonstrate the feasibility of large-scale, high-throughput genome mining by screening a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
185
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(204 citation statements)
references
References 53 publications
5
185
0
1
Order By: Relevance
“…There are many secondary metabolites that possess chemical modifications, functional groups, or structures that, coupled with the genome sequence, enable accurate prediction of the cognate biosynthetic gene cluster. These include glycosylated compounds (32), nonribosomal peptides (33), enediynes (34), phosphonates (35), and halogenated compounds (36). Identifying related clusters in multiple organisms is also becoming a widely accepted means of informatically characterizing a new gene cluster (for example, the cluster associated with tambromycin [37]).…”
Section: Discussionmentioning
confidence: 99%
“…There are many secondary metabolites that possess chemical modifications, functional groups, or structures that, coupled with the genome sequence, enable accurate prediction of the cognate biosynthetic gene cluster. These include glycosylated compounds (32), nonribosomal peptides (33), enediynes (34), phosphonates (35), and halogenated compounds (36). Identifying related clusters in multiple organisms is also becoming a widely accepted means of informatically characterizing a new gene cluster (for example, the cluster associated with tambromycin [37]).…”
Section: Discussionmentioning
confidence: 99%
“…http://dx.doi.org/10.1101/178673 doi: bioRxiv preprint first posted online Aug. 21, 2017; (Ju et al 2015) and the previously reported lips221 sequence (Zhang et al 2008) was downloaded from GenBank (ID: EF429087.1) (Benson et al 2013). Genomic DNA served as template for a polymerase chain reaction (PCR) to amplify out the genes.…”
Section: Cloning Of Wax Esterase Genesmentioning
confidence: 99%
“…Identification of Streptomyces species and the bioactive compound(s) they produce are complex and problematic [1][2][3][4]. Major obstacles in identifying Streptomyces species include horizontal gene transfer, erroneous reporting of species [5], recombination, chromosome rearrangement that may take place in Streptomyces [6,7], and replacing the scientific species name with a number Volume 1 | Issue 1…”
Section: Introductionmentioning
confidence: 99%
“…Streptomyces grouped based on 16S similarity must then be distinguished based on morphological, molecular features, signature protein(s), DNA "tags", and/or distinguishable character of a species may provide such a simple system of species identification [this work, [3][4][5][8][9][10]. Taddei et al [3] applied morphological and biochemical tests to differentiate between 71 isolates obtained from Venezuelan soils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation